PHENOMENA AND HISTORY OF ISLAMIC POLITICAL PARTIES IN INDONESIA - Yulianti, Nanik (Analisis: Jurnal Studi Keislaman, 2015)
Politics, coming back to its original meaning which might be defined  as influencing  other  people  and which  is involves  the making  of  a  common  decision  for  people,  then,  life  is  never politics-free.  When we are thinking,  we are contributing  in the political  life, how to influence or how to be influenced, how to make a decision in life or how to follow a decision. Politics contain of many dimensions,  one might  think  politics  in a negative  or positive way depending on which dimensions he stick the politics with. Political party is one of the main institutions in the political life which used in practicing the democracy as the representative system needed by the community.  It used as a media to transfer the political messages from the community  to the government, as peoples’ media to send their aspiration  to the people ‘above’, which existence is influencing the development of the policies of the country depending on its effectiveness. As a Muslim-Largest country,  Islam has a very important role in Indonesia’s political zone. Though,  not everything  that  has an “Islam” name is able to completely represent Islamic values and so some “non-Islam” might  also  represent  Islamic  ethical  values.  The  point  of this article is to focus more on how is the relationship between politics and Islam in Indonesia by observing the development  of Islamic Political Parties  and its phenomena. It will be well observed by the  historic-phenomenology  approach,  which  is describing  and observing the history of Islamic Political Parties in Indonesia and the social facts that happened in the society